Sketch of the Configuration Scheme of Two-stage Variable Speed Gear Transmission in Unmanned Helicopter Main Gearbox - Li Zhengminqing; Li Yingming; Wang Hao; Zhu Rupeng; Jin Guanghu (Jixie chuandong)
For unmanned helicopter economic cruises,main rotor speed changes could be significant. At present,the most effective method of changing the main rotor speed associated with the great speed range and low cost is a variable speed gear transmission employed in main gearbox. Thus,aiming at the speed difference of the helicopter main rotor during takeoff and cruise,the variable gear transmission is addressed and applied by western countries. According to the limited foreign literature,the configuration of two-stage variable speed gear transmission in unmanned helicopter are sketched,which would benefit to improve unmanned helicopter transmission system developments in China.